Tofacitinib in Combination With Methotrexate in Patients With Rheumatoid Arthritis: Clinical Efficacy, Radiographic, and Safety Outcomes From a Twenty-Four-Month, Phase III Study - van der Heijde, Désirée; Strand, Vibeke; Tanaka, Yoshiya; Keystone, Edward; Kremer, Joel; Zerbini, Cristiano A F; Cardiel, Mario H; Cohen, Stanley; Nash, Peter; Song, Yeong-Wook; Tegzová, Dana; Gruben, David; et al. (Arthritis & rheumatology, 2019)
OBJECTIVE: Tofacitinib is an oral JAK inhibitor for the treatment of rheumatoid arthritis (RA). The phase III, 24-month, placebo-controlled Oral Rheumatoid Arthritis (ORAL) Scan trial was undertaken to evaluate the efficacy, including inhibition of structural progression, and safety of tofacitinib in patients with active RA and an inadequate response to methotrexate (MTX). Month 24 data from the completed study are reported here. METHODS: Patients were randomized 4:4:1:1 to receive tofacitinib 5 mg or 10 mg twice daily, or placebo, switched to tofacitinib 5 mg or 10 mg twice daily, with stable background MTX. Patients receiving placebo switched to tofacitinib at month 3 (nonresponders) or month 6 (remaining patients). Clinical efficacy, structural progression, and treatment-emergent adverse events were evaluated. Analyses were performed on the full analysis set with observed data or nonresponder imputation with no advancement penalty for clinical efficacy, and imputation by linear extrapolation for structural progression. RESULTS: Overall, 797 patients were treated; 539 (67.6%) completed 24 months of treatment. Responses according to the American College of Rheumatology criteria for 20% improvement (ACR20), ACR50, and ACR70; the proportion of patients in whom remission or low disease activity was achieved according to the 4-variable Disease Activity Score in 28 joints using the erythrocyte sedimentation rate, Clinical Disease Activity Index, or Simplified Disease Activity Index; Boolean remission; and Health Assessment Questionnaire disability index scores were maintained from month 12 to 24 and were similar between tofacitinib dosages. Limited structural damage was observed at months 12 and 24. Safety events were similar in type and frequency for both tofacitinib dosages, and were consistent with those previously reported. CONCLUSION: Our findings indicate that clinical and radiographic treatment effects are sustained in months 12-24 in patients with RA receiving tofacitinib 5 mg or 10 mg twice daily plus MTX. The safety profile is consistent with that of other tofacitinib studies.
Keywords: dospělí; Arthritis, Rheumatoid; Female; pyrimidiny; revmatoidní artritida; Adult; výsledek terapie; ženské pohlaví; inhibitory Janus kinas; lidé; Janus Kinase Inhibitors; Treatment Outcome; Methotrexate; Male; Pyrroles; methotrexát; Piperidines; Antirheumatic Agents; kombinovaná farmakoterapie; lidé středního věku; mužské pohlaví; antirevmatika; pyrroly; Middle Aged; piperidiny; Pyrimidines; Drug Therapy, Combination; Humans